The Impact Of Islamic Social Finance (Zakat, Waqf, And Alms) On Rural Poverty Alleviation In Indonesia - Anez Yuniar Pradini; Nur’aini Nur’aini (Cirebon International Journal of Economics and Business, 2026)
Poverty in rural areas is a tangled thread triggered by specific characteristics, such as lack of access to infrastructure and low quality of human resources, so that its handling cannot be generalized to urban areas. Islamic Social Finance (ISF) offers alternative solutions through strategic instruments based on social justice. This qualitative research using the literature study method and descriptive analysis approach aims to analyze in depth the impact of the three main instruments of ISF—zakat, waqf, and alms—in alleviating village poverty, as well as evaluating productive ISF governance for the welfare of the local community. Data sourced from scientific articles, journals, books, and official reports are codified and analyzed using SWOT analysis techniques to formulate an applicable management strategy. The results of the study show that: 1) zakat contributes significantly to increasing income, job creation, and social transformation; 2) productive waqf has proven to be an effective and sustainable instrument in poverty alleviation; and 3) alms play a strong role in wealth redistribution, reducing inequality, and strengthening inclusive social solidarity. As an output, the SWOT analysis resulted in Strengths-Opportunities (SO)-based strategy recommendations, which include optimizing the ISF collection and distribution system, developing economic empowerment models through sharia communities and cooperatives, utilizing productive financing schemes, strengthening synergy between stakeholders, and measurably identifying local commodities and village potentials